ESSAY ABOUT LEGAL BLINDNESS: The State of Exception in a New Phase - is it really blindness? - Martinez, Vinício Carrilho; Scherch, Vinícius Alves (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
This article works on the hypothesis of a new phase of the State of Exception. The text is built in the form of an essay, since it deals with a reading of the blows that are given to the Constitution and that are produced by political subjects in comparison with legal aspects that can be placed as protectors of the normative order itself. It is necessary to observe permissive situations of exception and how this can affect the rule of law in the face of the behavior of political actors. The inductive methodology and bibliographic research were applied. The conclusion of the text is that there is a threat to normality that unfolds in the arbitrary exercise of power.